2013
DOI: 10.1016/j.pscychresns.2013.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Brain mechanisms for prepulse inhibition in adults with Tourette syndrome: Initial findings

Abstract: Prepulse inhibition (PPI) of the startle reflex is disrupted in a number of developmental neuropsychiatric disorders, including Tourette syndrome (TS). This disruption is hypothesized to reflect abnormalities in sensorimotor gating. We applied whole-brain functional magnetic resonance imaging (fMRI) to elucidate the neural correlates of PPI in adult TS subjects using airpuff stimuli to the throat to elicit a tactile startle response. We used a cross-sectional, case-control study design and a blocked-design fMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 81 publications
0
46
0
Order By: Relevance
“…Preferential involvement of the caudate in patients with Tourette syndrome has been demonstrated by various previous studies. [24][25][26][27] A particularly large cohort study showed a decreased volume of caudate nuclei in the Tourette syndrome-only group as compared to a Tourette syndrome þ obsessive compulsive disorder group, which demonstrated both a decrease in volume of the caudate and lentiform nuclei and implied that obsessive compulsive disorder symptomatology was more highly correlated with lentiform nuclei involvement. 28 This finding was supported by another study involving children with only obsessive compulsive disorder without comorbid behavioral or movement disorders, which found reduced volume of globus pallidus in these children.…”
Section: Discussionmentioning
confidence: 99%
“…Preferential involvement of the caudate in patients with Tourette syndrome has been demonstrated by various previous studies. [24][25][26][27] A particularly large cohort study showed a decreased volume of caudate nuclei in the Tourette syndrome-only group as compared to a Tourette syndrome þ obsessive compulsive disorder group, which demonstrated both a decrease in volume of the caudate and lentiform nuclei and implied that obsessive compulsive disorder symptomatology was more highly correlated with lentiform nuclei involvement. 28 This finding was supported by another study involving children with only obsessive compulsive disorder without comorbid behavioral or movement disorders, which found reduced volume of globus pallidus in these children.…”
Section: Discussionmentioning
confidence: 99%
“…Over the ensuing decades, a number of studies have tested our speculation of PPI deficits across multiple brain disorders and confirmed that – in addition to the reduction of PPI in schizophrenia populations, PPI is also impaired in cohorts of patients with OCD (Ahmari et al, 2012; Hoenig et al, 2005; Kohl et al, 2015; Swerdlow et al, 1993b), TS (Buse et al, 2016; Castellan Baldan et al, 2014; Castellanos et al, 1996; Swerdlow et al., 2001b; Zebardast et al, 2013), and HD (Munoz et al, 2003; Swerdlow et al, 1995; Valls-Solé et al, 2004). In addition, PPI deficits have been identified in other patient populations, including individuals with nocturnal enuresis (Ornitz et al, 1992), Asperger’s syndrome (Howlin and Murphy, 2002; McAlonan et al, 2002), 22q11 syndrome (Sobin et al, 2005), Kleinfelter syndrome (van Rijn et al., 2011), fragile-X syndrome (Frankland et al, 2004; Renoux et al, 2014; Yuhas et al, 2011), and blepharospasm (Gomez-Wong et al, 1998).…”
Section: Theme 1: Ppi Is Impaired Across Categorically Distinct Neuromentioning
confidence: 97%
“…27 Two studies have investigated the neural correlates of prepulse inhibition (PPI). 28,29 PPI is a neurological phenomenon in which a weaker prestimulus (prepulse) inhibits the reaction of an organism to a subsequent strong startling stimulus (pulse). A couple of studies indicate sensorimotor gating deficits in patients with TS.…”
Section: Functional Correlates Of Inhibitory Motor Controlmentioning
confidence: 99%
“…A couple of studies indicate sensorimotor gating deficits in patients with TS. 28,29 Buse et al 29 showed increased activity in five regions of the brain during PPI (middle frontal gyrus, the postcentral gyrus, the superior parietal cortex/ precuneus, the anterior cingulated gyrus, and the caudate body), and they suggested that this deficient sensorimotor gating in patients with TS might be associated with reduced recruitment of brain regions responsible for the higher-order integration of somatosensory stimuli.…”
Section: Functional Correlates Of Inhibitory Motor Controlmentioning
confidence: 99%